MicroRNA dilution during oocyte growth disables the microRNA pathway in mammalian oocytes - Kataruka, Shubhangini; Modrák, Martin; Kinterova, Veronika; Malik, Radek; Zeitler, Daniela M; Horvat, Filip; Kanka, Jiri; Meister, Gunter; Svoboda, Petr (Nucleic acids research, 2020)
MicroRNAs (miRNAs) are ubiquitous small RNAs guiding post-transcriptional gene repression in countless biological processes. However, the miRNA pathway in mouse oocytes appears inactive and dispensable for development. We propose that marginalization of the miRNA pathway activity stems from the constraints and adaptations of RNA metabolism elicited by the diluting effects of oocyte growth. We report that miRNAs do not accumulate like mRNAs during the oocyte growth because miRNA turnover has not adapted to it. The most abundant miRNAs total tens of thousands of molecules in growing (∅ 40 μm) and fully grown (∅ 80 μm) oocytes, a number similar to that observed in much smaller fibroblasts. The lack of miRNA accumulation results in a 100-fold lower miRNA concentration in fully grown oocytes than in somatic cells. This brings a knock-down-like effect, where diluted miRNAs engage targets but are not abundant enough for significant repression. Low-miRNA concentrations were observed in rat, hamster, porcine and bovine oocytes, arguing that miRNA inactivity is not mouse-specific but a common mammalian oocyte feature. Injection of 250,000 miRNA molecules was sufficient to restore reporter repression in mouse and porcine oocytes, suggesting that miRNA inactivity comes from low-miRNA abundance and not from some suppressor of the pathway.
Keywords: Cattle; Animals; skot; 3T3 Cells; křečci praví; Female; Oogenesis; teoretické modely; Gene Expression Regulation, Developmental; oogeneze; ženské pohlaví; druhová specificita; Oocytes; Mice; Species Specificity; oocyty; prasata; messenger RNA; kultivované buňky; myši; RNA, Messenger; Cells, Cultured; Swine; mikro RNA; buňky 3T3; krysa rodu Rattus; MicroRNAs; zvířata; Mice, Inbred C57BL; Models, Theoretical; vývojová regulace genové exprese; Rats; Cricetinae; myši inbrední C57BL